Changes in soil organic carbon fractions in abandoned croplands of Nepal - Ojha, Roshan Babu; Kristiansen, Paul; Atreya, Kishor; Wilson, Brian (Geoderma Regional, 2023)
Cropland abandonment in Nepal is an emerging land use change that has significant impacts on ecosystem functions, particularly soil organic carbon (SOC) pools and stocks. Information relating to SOC is limited for the mountainous terrain of Nepal that is subject to either SOC loss from erosion or SOC accumulation from secondary succession after cropland is abandoned. The rate of cropland abandonment is accelerating in Nepal but the impact of the abandoned duration on SOC, fractions, and SOC stock has not yet been investigated. We used a space-for-time substitution approach to assess the impacts of abandonment on SOC concentrations, stocks and associated pools of carbon across abandoned cropland (<5, 5–10, and > 10 years) compared with forest, pasture, and currently cropped land. Soil samples were collected at four depth increments (0–10, 10–20, 20–40, 40–60 cm). The change in SOC and stock was found to be significantly higher in the surface (0–20 cm) compared with sub-surface soil (20–60 cm) and consistently decreased with increasing soil depth under all land uses. Change in soil nitrogen concentration followed a similar pattern to that of SOC at all land uses and depths. Among the SOC fractions, particulate organic carbon increased significantly by a greater proportion compared to mineral-associated organic carbon and dissolved organic carbon after 10 years of cropland abandonment. Abandoned cropland >10 years had a higher SOC stock (64.19 Mg ha−1) in the soil profile (0–60 cm) compared with cropped land (58.76 Mg ha−1) although it remained lower than forest (66.56 Mg ha−1) and pasture (66.60 Mg ha−1) soils. Although there was a decrease in the first five years, there was a significant accumulation of SOC, associated fractions, and SOC stock after ten years of abandonment and colonisation by vegetation indicating the inception of ecosystem regeneration in abandoned croplands in the mountainous region of Nepal. •Study used space-for-time substitution examining SOC change with cropland abandonment.•Significant increase in SOC observed after 10 years of cropland abandonment.•Larger proportional change in particulate fraction than mineral-associated fraction.•The change in SOC and stock found higher in upper depth compared with deeper soils.•Secondary succession in abandoned cropland shows inception of ecosystem regeneration.